2001
DOI: 10.1074/jbc.m008567200
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome- and p38-dependent Regulation of ERK3 Expression

Abstract: Proteasome inhibition leads to accumulation of transcription factors, heat shock proteins, cyclins, and other proteasome substrate proteins by blocking their proteolytic degradation. An increase in gene transcription upon proteasome inhibition was found for a group of proteins, including p21 WAF1/CIP1 , ubiquitin, and transcription factors. In this study, we have demonstrated selective up-regulation of extracellular signal-regulated kinase 3 (ERK3) mRNA and protein expression upon treatment with peptide-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 33 publications
(34 reference statements)
3
17
0
Order By: Relevance
“…51 ERK3, also called p97, is activated by protein kinase C 52 and is responsive to different growth factors, implying a mechanism for specificity in cellular signaling 53 in response to activation of the p38 pathway. 54 As expected in a situation of tissue growth, we observed upregulation of RNA levels encoding ribosomal proteins and elongation factor-1␥, a protein involved in mRNA translation. Taken together, these changes in gene expression are in accordance with a situation of cell proliferation in response to extracellular stimuli associated with an HFD.…”
Section: Discussionsupporting
confidence: 77%
“…51 ERK3, also called p97, is activated by protein kinase C 52 and is responsive to different growth factors, implying a mechanism for specificity in cellular signaling 53 in response to activation of the p38 pathway. 54 As expected in a situation of tissue growth, we observed upregulation of RNA levels encoding ribosomal proteins and elongation factor-1␥, a protein involved in mRNA translation. Taken together, these changes in gene expression are in accordance with a situation of cell proliferation in response to extracellular stimuli associated with an HFD.…”
Section: Discussionsupporting
confidence: 77%
“…In this same group of genes, we also found downregulation of mRNA levels for ERK3, a mitogen-activated protein kinase present in the nucleus (9). ERK3, also called p97 or MAPK6, is responsive to different growth factors during activation of the p38 pathway (57). Downregulation of ERK3 may be a feedback control mechanism of cellular proliferation which attempts to slow down cellular proliferation during the process of ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 66%
“…A role for the proteasome in the regulation of ERK3 expression was recently reported by Zimmermann et al, who showed, by using a microarray-based differential cDNA hybridization technology, that ERK3 mRNA is upregulated by various proteasome inhibitors (58). Proteasome inhibition also resulted in the accumulation of ERK3 protein.…”
Section: Discussionmentioning
confidence: 93%